Improving Theory Building in Transformative Learning Pedagogical Research: Identity as an Illustrative Example - Cheryl K Baldwin (Adult Education Research Conference, 2025)
This conceptual paper argues that going beyond confirmatory findings in transformative learning (TL) research requires addressing some of the commonly misinterpreted aspects of qualitative research, and clarifying how curriculum-based studies can expand and build theory.
Keywords: Transformative Learning; Qualitative Research; Pedagogical Research; Identity